Draft Whole-Genome Sequences of 10 Enterotoxigenic Escherichia coli Serogroup O6 Strains - Pattabiraman, Vaishnavi (Genome Announc, 2015)
Enterotoxigenic Escherichia coli (ETEC) is an important cause of diarrhea in children under the age of 5 years and in adults living in developing countries, as well as in travelers to these countries. In this announcement, we release the draft whole-genome sequences of 10 ETEC serogroup O6 strains.